Design modification of the flow system of injection molds for rubber in the aspect of improving performance - Ziobro, J. (Видавництво Львівської політехніки, 2013)
The article shows problems connected with the process of injection molding of elastomers. It presents the analysis of the construction of the standard 16 cavities mold flow of injection mod to elastomers based on chloroprene rubber CR. It showed phenomena in this system. The results of the numerical simulation of injection molding have also been shown. The obtained results confirmed the possibility of the formation of defective products molded. We proposed an innovative design solution of this injection mold system. A large number of numerical simulation results for the modified flow system has been presented. Flow conditions in the channel have been improved. As a result, system volume has been reduced and a cycle of injection processing has been shortened. We eliminated the exploitation problems of mold. We reduced unit costs of manufactured products. Processing efficiency, safety and comfort have been improved.
Keywords: rubber; runner system; finite element analysis FEA; injection molds